Ben Jonson : vol. 5, volpone, or the fox epicoene, or the silent woman the alchemist catiline - Jonson, Ben; Jonson, Ben (Oxford : Clarendon press, 1954)
Poster for Federal Theatre Project presentation of "Volpone" at the Mayan Theatre, showing a skull with gold coins.
Keywords: Theatrical productions -- California -- 1930-1950.; Theatrical posters -- 1930-1950.; Screen prints -- Color -- 1930-1950.